FRI0475 Frequency and Predictors of Cardiovascular Events in A Bicentric Cohort of Psoriatic Arthritis from Spain. (15th July 2016) - Queiro, R.; Tejόn, P.; Morante, I.; Cabezas, I.; Brandy, A.; Alperi, M.; Belmonte, M.A.; Riestra, J.L.; Arboleya, L.; Ballina, J.
Abstract : Background: Cardiovascular (CV) comorbidity is frequent in psoriatic arthritis (PsA). This population shows a higher frequency of traditional CV risk factors (CVRF) when compared to normal population. However, additional traits related to the inflammatory nature of the disease may also suppose an additional risk beyond that attributable to classic CVRF. Objectives: To analyze the prevalence and predictors of CV events in a wide cohort of PsA patients recruited at two rheumatology departments from Spain. Methods: We included (cross-sectional) 340 PsA patients (CASPAR criteria) from two different rheumatology departments in Spain. There were 190 males and 150 females (mean age: 55 ± 13 yrs). Both subpopulations were similar in terms of age, sex distribution and disease duration. Prevalence and predictors of CV events (coronary heart disease, ictus and/or ischemic peripheral vascular disease) were analyzed. Initially, a univariate analysis was performed to examine unadjusted associations of potential risk factors. Significant variables in the univariate analysis were then introduced in a multivariate analysis with a backward stepwise approach. The statistical analysis software package used was SPSS v.19.0. Patients gave their informed consent and an institutional ethics committee approved the final version of the study. Results: Distribution of classic CVRF was as follow: Diabetes 14%, hypertension 36%, dyslipidemia 31%, tobacco 27%, obesity 35% and 24% had overweight. Thirty two out of 340 subjects (9.4%) developed 41 CV events: 15 coronary events, 15 ictus and 11 events of ischemic peripheral vascular disease. Compared to men, women had more diabetes (29.5% vs. 18%, p=0.049) and obesity (44% vs. 29%, p=0–010), even though the frequency of CV events did not differ between sexes. In multivariate analysis, an age of psoriasis onset ≥40 yr (OR 4.1, 95%CI: 1.04–16.2, p<0.001) and dyslipidemia (OR 5.8, 95%CI: 1.5–22.8, p<0.001) were found independently related to the risk of coronary events. Hypertension was an independent predictor of ictus (OR 8.0, 95%CI: 1.7–38.1, p<0.001). When analyzing CV events as a whole, an age of psoriasis onset ≥40 yr (OR 3.4, p=0.03), a polyarticular pattern during evolution (OR 2.9, p=0.04), hypertension (OR 5.3, p=0.007) and dyslipidemia (OR 2.6, p=0.07), were found independently associated to the risk of CV events in multivariate analysis. Conclusions: In our context, CV comorbidity of PsA may be explained by a conjunction of classic CVRF, late onset of psoriasis, and the inflammatory burden of joint disease. A better management of these factors should be the basis for improvement of CV health of these patients References: Ogdie A, Yu Y, Haynes K, Love TJ, Maliha S, Jiang Y, et al. Risk of major cardiovascular events in patients with psoriatic arthritis, psoriasis and rheumatoid arthritis: a population-based cohort study. Ann Rheum Dis 2015; 74:326–32. Horreau C, Pouplard C, Brenaut E, Barnetche T, Misery L, Cribier B, et al. Cardiovascular morbidity and mortality in psoriasis and psoriatic arthritis: a systematic literature review. JEADV 2013; 27 (Suppl. 3):12–29. Disclosure of Interest: None declared